Fall risk screening: Audiologists’ perceived knowledge, views and reported practice - Kayla J. McFarlane; Amisha Kanji; Alida Naude (South African Family Practice)
Background: Falls among older adults are a major public health issue. In South Africa, where the elderly population is expected to quadruple within the next three decades, fall prevention is critical.